Experience with a trigger tool for identifying adverse drug events among older adults in ambulatory primary care. Issue 3 (24th May 2009) - Singh, R; McLean-Plunckett, E A; Kee, R; Wisniewski, A; Cadzow, R; Okazaki, S; Fox, C; Singh, G
Abstract : Objective: To evaluate the performance of a trigger tool for identifying adverse drug events (ADEs) among older adults in ambulatory primary care practices. Methods: Manual 12-month retrospective chart review at six practices using a 39-item trigger tool. Patients aged 65 or above with cardiovascular diagnoses were included. Charts with triggers underwent detailed review by a physician and pharmacist to identify ADEs. Results: Of 1289 charts reviewed, 645 (50%) had at least one trigger. A random sample of 383 of these charts underwent further review (mean 64 charts per practice). Among the 908 triggers in these charts, 232 were deemed to represent ADEs, of which 92 were deemed preventable and 30% of these were severe. The most common triggers and their positive predictive values (PPVs) for ADEs were "Medication stop" (26.3%), "Hospitalisation" (21.8%) and "Emergency Room" visit (14.9%). Only nine of the triggers had PPVs >5%. These nine triggers accounted for 94.4% (219/232) of the ADEs detected. Discussion: Trigger tools have a potential role in driving quality improvement in ambulatory primary care. In our study using a 39-item ADE trigger tool, most triggers had very low PPVs. Nine of the 39 triggers accounted for 94.4% of ADEs detected, suggesting the possibility of a much briefer tool. Practical issues related to adoption of such tools by practising physicians should be further explored.